2021
DOI: 10.1007/s10792-021-01952-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: more than a respiratory virus, an optical coherence tomography study

Abstract: Purpose The purpose of this study is to investigate anatomic and morphologic features of inner and outer retinal layers in patients recovered from COVID-19 with Spectral Domain Optical Coherence Tomography (SD-OCT), whether correlate with any symptoms during disease process. Methods 32 patients recovered from COVID-19 and age- and gender-matched 36 healthy controls were included in this cross-sectional study. Ganglion cell-inner plexiform layer, macular and peripapiller… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Alterations in retinal layers of patients recovered from COVID-19 were demonstrated with this study, providing that COVID-19 infection had both temporary and persistant effects in retina in early and long-term periods. At the beginning of the pandemic, thinking to be only a respiratory system virus, making an acute infection, the agent is named as Severe Acute Respiratory Syndrome Coronavirus, letter R represents respiratory, but it is shown that it is more than a respiratory virus [ 4 6 ], and letter A represents Acute, nevertheless it seems to be a chronic infection. As COVID-19 pandemic continues and the infected population grows, reports of persistent and prolonged effects after COVID-19 are increasing, those are need to be identified and classified [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations in retinal layers of patients recovered from COVID-19 were demonstrated with this study, providing that COVID-19 infection had both temporary and persistant effects in retina in early and long-term periods. At the beginning of the pandemic, thinking to be only a respiratory system virus, making an acute infection, the agent is named as Severe Acute Respiratory Syndrome Coronavirus, letter R represents respiratory, but it is shown that it is more than a respiratory virus [ 4 6 ], and letter A represents Acute, nevertheless it seems to be a chronic infection. As COVID-19 pandemic continues and the infected population grows, reports of persistent and prolonged effects after COVID-19 are increasing, those are need to be identified and classified [ 12 – 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the lungs are the main target organ, it has potential to infect other organs and ocular tissues as well [ 4 6 ]. The virus gains entry to host cell by binding to angiotensin converting enzyme-2 (ACE-2), which is widely expressed in human cells [ 1 , 7 ] and can cause endothelial dysfunction associated with apoptosis, either by direct viral infection of the endothelium or by immune-mediated response [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17] One research found macular RNFL thickness in patients recovering from COVID-19 compared to healthy subjects. [18] Another study also showed localized thinning of RNFL in patients with COVID-19. [19] In contrast, our study could not observe a different outcome in COVID-19 patients regarding RNFL.…”
Section: Discussionmentioning
confidence: 98%
“…A retrospective cohort study compared the thickness of retinal layers in recovered COVID-19 patients with non-infected individuals; it found that 19 out of 32 recovered patients demonstrated a thinner retinal nerve-fiber layer compared to 36 of the control group. The visual implications of this finding were inconclusive but the thinning was more pronounced amongst patients complaining of associated ocular pain rather than being asymptomatic [6].…”
Section: Posterior Segment Findingsmentioning
confidence: 93%